Analyzing the effectiveness of Team Behaviour using TPB model in IT Sector (International Journal of Food and Nutritional Sciences, 2022)
Purpose – The purpose of this study is to examine the effectiveness of team behaviour using the Theory of Planned Behaviour (TPB) model, which states that attitudes, subjective norms, and perceived behavioural control influence individual intentions to engage in a certain behaviour. This study adopts a comprehensive research technique to evaluate the elements that influence team members' intentions to exhibit cooperative behaviour within their individual teams. Design/methodology/approach – The study was carried out using the advanced framework of behavioural model. The questionnaire was prepared and distributed among 371 employees working in an IT sector. The population was selected using stratified ramdom sampling. Findings – While analyzing the TPB factors withTeam Bahaviour, the findings confirm that the factors have a strong and positive impact on behaviours of employees within the team. It is also noted that the age and experience have a significant relation with attitude and subjective norms.